(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2023)
The article provides important recommendations based on empirically tested information and results of working gaps in mastering new knowledge or skill on the basis of accurate diagnosis in order to increase the level of mastering the lessons of students.